2006
DOI: 10.1206/0003-0082(2006)3532[1:mensot]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Extremes—Two New Snakes of the Genus Atractus from Northwestern South America (Colubridae: Dipsadinae)

Abstract: Two new Andean snakes exhibit extreme morphology in a genus of South American dipsadine colubrids. One, Atractus attenuatus, new species, is a slender, exceptionally attenuated snake 420 mm in total length (adult male holotype), with 17 scale rows, a high ventral + subcaudal count (226), and an extremely vague pattern of numerous, closely spaced, indistinct dark crossbars on a brown ground color. Atractus attenuatus comes from 1000 m elevation in the northern end of the Cordillera Central (Sabanalarga, Antioqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 3 publications
2
12
0
5
Order By: Relevance
“…Despite of improvements on the fieldwork and facilities to examine specimen collections in the past 50 years, the actual scenario have not much change and many species still named on the basis of single individuals (Myers, 2003;Silva, 2004;Esqueda and La Marca, 2005; Jorge da Silva et al, 2005;Myers and Schargel, 2006;Myers and Donnelly, 2008;Passos and Fernandes, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite of improvements on the fieldwork and facilities to examine specimen collections in the past 50 years, the actual scenario have not much change and many species still named on the basis of single individuals (Myers, 2003;Silva, 2004;Esqueda and La Marca, 2005; Jorge da Silva et al, 2005;Myers and Schargel, 2006;Myers and Donnelly, 2008;Passos and Fernandes, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have advocated that apparent rarity of most Atractus species was due to their secretive habits or endemism (Savage, 1960;Schargel and García-Pérez, 2002;Myers, 2003;Myers and Schargel, 2006). Passos, CisnerosHeredia and Salazar-V (2007) pointed out that study of museum specimen's revealed several Atractus species to be common rather than rare within certain distributional range.…”
Section: Discussionmentioning
confidence: 99%
“…En Ecuador se encuentra distribuida en los bosques siempreverdes montanos bajos y bosques de neblina montanos al occidente de los Andes, en las provincias de Cotopaxi y Pichincha, en altitudes entre 1680 y 2307 m [26][27][28][29]. En el DMQ, esta especie ha sido encontrada en la parroquia de Nanegal (Bosque Protector Santa Lucía), a 2307 m de altitud [29].…”
Section: Atractus Gigas Myers Y Schargel 2006unclassified
“…
Wagler, 1828 is the most speciose genus of snakes in the world, with 143 valid species, from which 18 have been described in the course of the present decade (Uetz et al, 2019). With the exception of a single species present in Gorgona Island (A. medusa), this genus is confined almost entirely to the South American mainland, extending northward only to Central Panama (Myers & Schargel, 2006;Passos et al, 2009b;Wallach et al, 2014). However, the greatest diversity of the genus occurs in the Andes, particularly in Colombia, the country with the highest diversity of Atractus, with 64 species recorded (40
…”
mentioning
confidence: 99%